Multilayer crypto method using playing cards shuffling operation - J. Rasras, Rashad; Rasmi Abu Sara, Mutaz; Alqadi, Ziad (Bulletin of Electrical Engineering and Informatics, 2025)
An efficient and highly secure method of secret message cryptography will be presented which based on the principle of playing cards shuffling. The method will be implemented in a selected number of layers, each layer will encrypt-decrypt the input message using its own private key (PK), the output of any layer can be taken as a final encrypted-decrypted message, increasing the number of layers will increase the security level of the massage, making the hacking attacks impossible. In the encryption function a key generation and a message blocks shuffling will be executed, while in the decryption function the key generation and the message blocks reverse shuffling will be executed. The PK used in this method will be complicated and it will contain for each layer 2 chaotic parameters (r and x) and the block size (BS), utilizing these parameters, a chaotic logistic map model is run to produce a chaotic key, which is sorted to produce the layer's index key. Applying 4 layers the length of confidential key will be 768 bits, this length will be able to generate a large key space which is robust to hacking attempts. The speed parameters and throughput of the proposed will be calculated and compared with those of other methods.